Dossier on Govan Young: Exploring children's historical consciousness through film and archaeology. Issue 2 (30th November 2018) - Archibald, David; Driscoll, Stephen; Doherty, Catherine; Perry, Mia
Govan Young (2017) is a 30-minute documentary in which schoolchildren from Glasgow learn of the area's important but largely unknown medieval history. This dossier brings together four essays that reflect on the film from various academic perspectives – film studies, archaeology and education – to explore how schoolchildren might learn about the past, and develop a historical consciousness, by participating in film-making projects. The dossier also reflects on how educators can learn from those whom they are supposedly teaching, thereby highlighting that experimental pedagogical projects often bring unexpected learning outcomes into being. Consequently, educators must resist the pressures to predict the outcomes of projects, and must strive to keep the future open-ended.